1992
DOI: 10.1259/0007-1285-65-777-766
|View full text |Cite
|
Sign up to set email alerts
|

Transverse geniculate ligament of the knee: appearance and frequency on plain radiographs

Abstract: The aims of the study were to determine the frequency of visualization of the normal transverse geniculate ligament (TGL) of the knee on lateral plain radiographs with magnetic resonance imaging (MRI) as a reference, and to determine features that make this ligament apparent on plain radiographs. 50 consecutive lateral plain radiographs and sagittal T1-weighted images of corresponding knees were evaluated prospectively. A TGL was considered visualized on plain radiographs when an opacity of soft-tissue density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
1
11
0
1
Order By: Relevance
“…Several cadaveric and imaging studies of this ligament have been made and it has been shown to be of variable thickness when present [4,5,6,7,8,9]. In a recent cadaveric study, three distinct types of AIL were described with regard to its insertion on or near the anterior horns of the menisci [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several cadaveric and imaging studies of this ligament have been made and it has been shown to be of variable thickness when present [4,5,6,7,8,9]. In a recent cadaveric study, three distinct types of AIL were described with regard to its insertion on or near the anterior horns of the menisci [4].…”
mentioning
confidence: 99%
“…The AIL can sometimes be depicted in a lateral knee radiograph when there is enough surrounding fat to create adequate contrast around it [7,8]; however, it is with MR imaging that the AIL can best be visualized non-invasively. When present, this ligament is usually seen easily in the anterior part of the knee joint as a lowintensity band in MR imaging examinations of the knee [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This structure is also called the transverse geniculate ligament, meniscomeniscal ligament, anterior transverse ligament, and intermeniscal ligament. There have been a few studies considering its properties on plain radiography and on magnetic resonance imaging (MRI) [5,6,8]. Watanabe et al [8] retrospectively reviewed sagittal MRI findings of 200 knees to determine the frequency with which normal ligamentous and tendinous structures mimic pathological changes within the knee.…”
Section: Introductionmentioning
confidence: 99%
“…They then confirmed this by MRI. Another study by the same authors [6] prospectively evaluated findings by lateral plain radiography and sagittal MRI in 50 consecutive knees and in the corresponding knees. They found that anterior intermeniscal ligament was visible in 12% of cases by plain radiography and 58% of cases by MRI.…”
Section: Introductionmentioning
confidence: 99%